Burnout among German oncologists: a cross-sectional study in cooperation with the Arbeitsgemeinschaft Internistische Onkologie Quality of Life Working Group : original article : clinial oncology - Helaß, Madeleine; Haag, Georg Martin; Bankstahl, Ulli Simone; Gencer, Deniz; Maatouk, Imad (Journal of cancer research and clinical oncology, 2023)
Oncologists are at an increased risk of developing burnout, leading to negative consequences in patient care and in professional satisfaction and quality of life. This study was designed to investigate exhaustion and disengagement among German oncologists and assess the prevalence of burnout among oncologists within different professional settings. Furthermore, we wanted to examine possible relations between sociodemographic factors, the oncological setting, professional experience and different aspects of burnout.